Unveiling the impact of CDK8 on tumor progression: mechanisms and therapeutic strategies - Yin, Xiaomin; He, Zhilong; Chen, Kun; Ouyang, Kai; Yang, Changxuan; Li, Jianjun; Tang, Hailin; Cai, Manbo (Frontiers in Pharmacology, 2024)
CDK8 is an important member of the cyclin-dependent kinase family associated with transcription and acts as a key "molecular switch" in the Mediator complex.CDK8 regulates gene expression by phosphorylating transcription factors and can control the transcription process through Mediator complexes. Previous studies confirmed that CDK8 is an important oncogenic factor, making it a potential tumor biomarker and a promising target for tumor therapy. However, CDK8 has also been confirmed to be a tumor suppressor, indicating that it not only promotes the development of tumors but may also be involved in tumor suppression. Therefore, the dual role of CDK8 in the process of tumor development is worth further exploration and summary. This comprehensive review delves into the intricate involvement of CDK8 in transcription-related processes, as well as its role in signaling pathways related to tumorigenesis, with a focus on its critical part in driving cancer progression.